(untitled) (Philological Studies, 2019)
This article discuss position of tree within spatial models in oral lyric. Tree participates in poetic modeling of space in motives of planting and fencing when it represents landmark, which directs human world. It can be located in the center or at the periphery of one’s own or alien space (as a part of the house, village or town) or it can be sign of the boundary between these worlds, between earthly and unearthly space (as a sign of wilderness, a part of mountain/forest). Regardless from which side of the boundary it is planted, tree is a mark of sacred as a place of isolation or oath, as an aim or place of initiation task (planting, guarding the fruits, quest, ritual dance), as a ritual place. Since tree has marked position in traditional model of the world and since it is tightly connected with sacred, it is opportune to discuss existence of sign-tree as analogues to the sign-place.